Representation of Cultural Identity of Bangkalan Community through Semiotic Analysis of Halal Culinary Tourism - Qadrina Lailyn Amrullah; Desi Puspitasari (Universitas Muhammadiyah Kalimantan Timur, 2023)
Bangkalan is one of the preferred tourist destinations in East Java because of its culture and culinary diversity. However, discussions about culinary are inseparable from culture. To raise public awareness of the cultural heritage richness of Bangkalan halal culinary, an analysis related to culture and culinary has to be carried on. This research aimed to analyze the semiotic and philosophical meaning of Bangkalan's halal culinary (Tajin Sobih, Nasi Serpang, and Topak Ladeh), which represents the cultural identity of Bangkalan people. This research is qualitative descriptive with a semiotic analysis approach of Charles Peirce's triadic model to analyze the visual composition of food. Data collection techniques used are observation, interviews, and documentation. Data analysis was carried out by processing signs and symbols in words into meaningful information. From the result analysis, it can be affirmed that each culinary has a variety of meanings that represent the value of community unity, prosperity, friendship, togetherness, and cultural heritage richness of Bangkalan people. The strengths of the three culinary arts are in the form of historical content, philosophical values, and religious beliefs so that they can foster public interest in visiting Bangkalan.